0\; ,\\\\2^{log_3x}\cdot 2^3-5\cdot x^{log_32}-24=0\\\\\\\star a^{log_{b}c}=\Big [\; a=c^{log_{c}a}\; \Big ]=\Big (c^{log_{c}a}\Big )^{log_{b}c}=c^{log_{c}a\, \cdot \, log_{b}c}=\Big [\; log_{b}c=\frac{1}{log_{c}b}\; \Big ]=\\\\=c^{\frac{log_{c}a}{log_{c}b}}=\Big [\; log_{b}a=\frac{log_{c}a}{log_{c}b}\; \Big ]=c^{log_{b}a}\; \; \Rightarrow \; \; \boxed {a^{log_{b}c}=c^{log_{b}a}}\; \; \star \\\\\\8\cdot 2^{log_3x}-5\cdot 2^{log_3x}-24=0" alt="2^{log_3x+3}-5\cdot x^{log_32}-24=0\; ,\; \; ODZ:\; x>0\; ,\\\\2^{log_3x}\cdot 2^3-5\cdot x^{log_32}-24=0\\\\\\\star a^{log_{b}c}=\Big [\; a=c^{log_{c}a}\; \Big ]=\Big (c^{log_{c}a}\Big )^{log_{b}c}=c^{log_{c}a\, \cdot \, log_{b}c}=\Big [\; log_{b}c=\frac{1}{log_{c}b}\; \Big ]=\\\\=c^{\frac{log_{c}a}{log_{c}b}}=\Big [\; log_{b}a=\frac{log_{c}a}{log_{c}b}\; \Big ]=c^{log_{b}a}\; \; \Rightarrow \; \; \boxed {a^{log_{b}c}=c^{log_{b}a}}\; \; \star \\\\\\8\cdot 2^{log_3x}-5\cdot 2^{log_3x}-24=0" align="absmiddle" class="latex-formula">
![3\cdot 2^{log_3x}=24\\\\2^{log_3x}=8\\\\2^{log_3x}=2^3\\\\log_3x=3\\\\x=3^3\\\\x=27 3\cdot 2^{log_3x}=24\\\\2^{log_3x}=8\\\\2^{log_3x}=2^3\\\\log_3x=3\\\\x=3^3\\\\x=27](https://tex.z-dn.net/?f=3%5Ccdot%202%5E%7Blog_3x%7D%3D24%5C%5C%5C%5C2%5E%7Blog_3x%7D%3D8%5C%5C%5C%5C2%5E%7Blog_3x%7D%3D2%5E3%5C%5C%5C%5Clog_3x%3D3%5C%5C%5C%5Cx%3D3%5E3%5C%5C%5C%5Cx%3D27)